International Classification Systems for Trade in Services: Development, Structure and Implementation - Bagaria, Ram Lal (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
The services trade classification systems have evolved over time by international organizations, researchers and professionals working in the field. This research paper traces historical development of such classification systems from the beginning. The paper also highlights current frameworks and standards of services trade classifications at a global level. This paper focuses on concerned manuals, such as CPC, W/120, BPM6, MSITS 2010, EBOPS 2010, etc. EBOPS 2010 divides services into 12 categories including but not limited to manufacturing services, intellectual property services and digital services. The paper also highlights contemporary challenges in services classification due to increasing digital services transactions.